Pathogenic bacterial species and the microbiome of cat fleas (Ctenocephalides felis) inhabiting flea-infested homes - Taylor E. Gin; Charlotte O. Moore; Trey Tomlinson; Grace Wilson; Amiah Gray; Cameron Sutherland; Kamilyah Miller; Krista Li; Michael Canfield; Brian Herrin; Erin Lashnits; Benjamin Callahan (PLoS ONE, 2026)
Background Ctenocephalides felis is a common ectoparasite of dogs and cats and can transmit a variety of pathogens including Bartonella and Rickettsia species. These bacteria, along with the known endosymbiont Wolbachia , are well-documented members of the C. felis microbiome, but species-level information is limited. Additionally, little is known about the variation in the C. felis microbiome in fleas from different sources and when different sequencing methods are applied to the same samples. Objective This study aimed to characterize the flea microbiome using both short-read (V3/V4) and long-read (full-length) 16S rRNA gene sequencing, determine whether long-read sequencing improves species-level identification especially in known pathogenic genera, and evaluate differences in microbial composition between fleas collected from cats, dogs, and environmental traps. Methods Fleas were collected from cats, dogs, and traps in flea-infested homes in Florida, pooled by source, and sequenced using short- (V3/V4) and long-read (full-length) 16S rRNA gene sequencing. Microbial prevalence and abundance were compared across sequencing approaches. Community composition was evaluated for differences between sources and houses. Candidate members of the flea microbiome were identified based on a combination of prevalence, abundance, and statistical signatures of potential contaminant origin. For Rickettsia and Bartonella , species-level taxonomic assignments were refined using a phylogenetic approach. Results Wolbachia , Rickettsia , and Bartonella were the most prevalent and abundant taxa. Spiroplasma was identified as a fourth core member of the flea microbiome. Long-read sequencing enabled better, but not perfect, species-level classification of Bartonella and Rickettsia compared to short-read sequencing. Important relationships between specific ASVs and flea sources were identified, for example fleas from cats harbored higher abundances of B. clarridgeiae and B. henselae than fleas from traps.